MiR‐214 is an important regulator of the musculoskeletal metabolism and disease - Youqiang Sun; Vincent Kuek; Yuhao Liu; Jennifer Tickner; Yu Yuan; Leilei Chen; Zhikui Zeng; Min Shao; Wei He; Jiake Xu (2018)
MiR‐214 belongs to a family of microRNA (small, highly conserved noncoding RNA molecules) precursors that play a pivotal role in biological functions, such as cellular function, tissue development, tissue homeostasis, and pathogenesis of diseases. Recently, miR‐214 emerged as a critical regulator of musculoskeletal metabolism. Specifically, miR‐214 can mediate skeletal muscle myogenesis and vascular smooth muscle cell proliferation, migration, and differentiation. MiR‐214 also modulates osteoblast function by targeting specific molecular pathways and the expression of various osteoblast‐related genes; promotes osteoclast activity by targeting phosphatase and tensin homolog (Pten); and mediates osteoclast‐osteoblast intercellular crosstalk via an exosomal miRNA paracrine mechanism. Importantly, dysregulation in miR‐214 expression is associated with pathological bone conditions such as osteoporosis, osteosarcoma, multiple myeloma, and osteolytic bone metastasis of breast cancer. This review discusses the cellular targets of miR‐214 in bone, the molecular mechanisms governing the activities of miR‐214 in the musculoskeletal system, and the putative role of miR‐214 in skeletal diseases. Understanding the biology of miR‐214 could potentially lead to the development of miR‐214 as a possible biomarker and a therapeutic target for musculoskeletal diseases.